2021
DOI: 10.1016/j.eclinm.2021.100761
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in COVID-19 mortality across Michigan, United States

Abstract: Background: Black populations in the United States are being disproportionately affected by the COVID-19 pandemic, but the increased mortality burden after accounting for health and other demographic characteristics is not well understood. We examined characteristics of individuals who died from COVID-19 in Michigan by race stratified by their age, sex and comorbidity prevalence to illustrate and understand this disparity in mortality risk. Methods: We evaluate COVID-19 mortality in Michigan by demographic and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 30 publications
1
30
0
4
Order By: Relevance
“…Our results indicate that a SARS-CoV-2 variant with higher transmissibility compared to the currently circulating strain would become dominant within two months of being introduced. Our findings are consistent with prior studies that indicated that the variant alpha would become the predominant variant in the US, 2–3 months after introduction [ 3 , 41 ]. Even in the presence of SARS-CoV-2 variants, a vaccination program was shown to have potential in significantly reducing the disease burden associated with COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicate that a SARS-CoV-2 variant with higher transmissibility compared to the currently circulating strain would become dominant within two months of being introduced. Our findings are consistent with prior studies that indicated that the variant alpha would become the predominant variant in the US, 2–3 months after introduction [ 3 , 41 ]. Even in the presence of SARS-CoV-2 variants, a vaccination program was shown to have potential in significantly reducing the disease burden associated with COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…10 Distrust in medical providers or financial barriers as previously discussed may play a role. 10 Black Americans also comprise a disproportionate percentage of frontline jobs where risk of exposure is high, including nursing homes or skilled care facilities, courier services, and urban transportation. 13 Patients with disabilities were also more likely to be MV from COVID-19.…”
Section: Key Resultsmentioning
confidence: 99%
“… 9 Financial insecurity and lack of insurance may also delay seeking medical care until advanced stages of infection. 10 Accordingly, we were surprised to find that patients under the “Not employed” category did not have a higher risk of MV. This could be a limitation of the EMR if employment history is not updated.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations